'Failed' tidal disruption events and X-ray flares from the Galactic Centre. Issue 2 (5th April 2019) - Sacchi, Andrea; Lodato, Giuseppe
Abstract: The process of tidal disruption of stars by a supermassive black hole provides luminous UV and soft X-ray flares with peak luminosities of ≈10 46 erg s −1 and duration of a few months. As part of a wider exploration of the effects of stellar rotation on the outcome of a TDE, we have performed hydrodynamical simulations of the disruption of a rotating star whose spin axis is opposite to the orbital axis. Such a retrograde rotation makes the star more resilient to tidal disruption, so that, even if its orbit reaches the formal tidal radius, it actually stays intact after the tidal encounter. However, the outer layers of the star are initially stripped away from the core, but then fall back on to the star itself, producing a newly formed accretion disc around the star. We estimate that the accretion rate on to the star would be strongly super-Eddington (for the star) and would result in an X-ray flare with luminosity of the order of ≈10 40 erg s −1 and duration of a few months. We speculate that such events might be responsible for the known X-ray flares from Sgr A* in the recent past.